FACTORS RELATED TO ANEMIA DURING PREGNANCY AT UTEUN PULO COMMUNITY HEALTH CENTERNAGAN RAYA REGENCY - Elly Surya Dasni; Heru Subaris Kasjono; Gunarmi (Jurnal Penelitian, 2026)
Background: Anemia is a global maternal health problem. It occurs in both developed and developing countries, including Indonesia. Anemia impacts health, human resources, and social and economic development. Most cases of anemia in Indonesia are caused by iron deficiency, thus also called iron deficiency anemia. The prevalence of anemia varies based on age, gender, physiological and pathological conditions, environmental factors, social and economic factors, breakfast habits, demographics, Body Mass Index (BMI), and life stage. Purpose to determine the factors associated with anemia in pregnancy at the Uteun Pulo Community Health Center, Nagan Raya Regency. Method: . Cross-sectional research design. The sampling technique was accidental sampling of 82 people. Univariate and bivariate data analysis using the chi-square test. Results: the study showed that the p-value of the 5 independent variables studied, namely compliance with iron tablet consumption (0.000), parity (0.825), birth spacing (0.713), nutritional status (0.009) and infectious diseases (0.001) so that it can be concluded that 3 variables have a relationship with anemia in pregnancy, namely compliance with iron tablet consumption, nutritional status, and infectious diseases. Then the most dominant variables influencing are the variables of iron tablet consumption and infectious diseases.